Novel 3-(1H-indol-3-yl)-2-[3-(4-methoxyphenyl)ureido]propanamides as selective agonists of human formyl-peptide receptor 2. Issue 14 (15th July 2015) - Lacivita, Enza; Schepetkin, Igor A.; Stama, Madia L.; Kirpotina, Liliya N.; Colabufo, Nicola A.; Perrone, Roberto; Khlebnikov, Andrei I.; Quinn, Mark T.; Leopoldo, Marcello
Graphical abstract: Abstract: N -Formyl peptide receptors (FPRs) are G protein-coupled receptors (GPCRs) that play critical roles in inflammatory reactions, and FPR-specific interactions can possibly be used to facilitate the resolution of pathological inflammatory reactions. We here report the synthesis and biological evaluation of six pairs of chiral ureidopropanamido derivatives as potent and selective formyl peptide receptor-2 (FPR2) agonists that were designed starting from our lead agonist ( S )-3-(1 H -indol-3-yl)-2-[3-(4-methoxyphenyl)ureido]- N -[[1-(5-methoxy-2-pyridinyl)cyclohexyl]methyl]propanamide (( S )-9a ). The new compounds were obtained in overall yields considerably higher than ( S )-9a . Several of the new compounds showed agonist properties comparable to that of ( S )-9a along with higher selectivity over FPR1. Molecular modeling was used to define chiral recognition by FPR2. In vitro metabolic stability of selected compounds was also assessed to obtain preliminary insight on drug-like properties of this class of compounds.